Penggunaan E-Book Badi (Buku Animasi Dakwah Islami) Sebagai Media Dakwah Siswa SD - Nur Aeni , Ani; Inaydamariny , Annisa; Agustin, Ninda; Rachmawanti , Khofifah (Perspektif Ilmu Pendidikan, 2023)
Every human being should be able to practice all forms of morality, both for himself and for others in everyday life without exception. The development of the BADI e-book (Animated Islamic Da’wah Book) can be used as a da’wah medium to improve the good morals of elementary school students, especially in the aspect of honesty. This e-book is based on Islamic religious education and uses the story of the preaching of the prophet Muhammad SAW as a model of commendable morals for students presented in animated stories. The research was conducted in March on students of SDN Sukanandur, Kab. Sumedang and involve teachers as experts to assess and provide input regarding the products made. Based on the results of observations that have been made, it was found that this e-book can; 1) Support students in independent learning, 2) Increase student motivation, 3) Make it easier for students to understand the material, 4) Learning activities become more effective, 5) Increase student enthusiasm, 6) Help students remember material. Both teachers and schools need to work together to create learning that is able to improve students’ commendable morals.